Törésvonalak, I-II - Schiffer, Pál (Hungary, 1998)
The film shows the transition period in Hungary during the early 90s. It starts with the mass redundancies in the Videoton factory in Székesfehérvár in 1989 and through the next several years follows the ups and downs of several of the sacked workers, their struggle to find new jobs and make a living during the economic crisis. Some of them are more successful than others.
Keywords: Documentary films